Integration of Electrostatic Precipitator-Ionizer-HEPA Filter for a Low Power Air Filtration System - Arif Budianto; Mira Andini; Kasnawi Al Hadi; Laili Mardiana; Nurul Qomariyah; Lalu Sahrul Hudha; Titi Devitanala (Lembaga Bale Literasi, 2026)
Air pollution has become an important issue due to its impacts on human health and the environment. Especially indoor air pollution has more attached many concerns because humans also spend their time every day indoors. Indoor air pollutants in terms of particulate matter (PM) in different size distribution and gasses come from different sources such as smoke, hair spray, mosquito disinfectant, cooking, etc. The air purifier has become popular in the pandemic era at the being. In this research, we developed an indoor PM purification system technology by integrating three filtering methods: HEPA filter, electrostatic precipitator, and an ionizer to clean air by reducing PM concentration. The purpose of this study is to obtain the indoor purification system capable of cleaning non-bioaerosol PMs. The investigation was conducted in a chamber using several particulate matter sources. From both PM sources, it can be concluded that the purification system works well to purify the air in the tested chamber. The measurements of the different PM size distribution concentrations show that the system has the purification efficiency of 90±1% (non-bio fine particle) and 91±1% (non-bio coarse particle).